Alokasi Waktu Tenaga Kerja dan Kelayakan Usaha Agroindustri Grubi di Tawangmangu Karanganyar, Indonesia - Muri Aditama; Umi Barokah; Raden Kunto Adi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Tawangmangu District has high sweet potato productivity, which is processed into grubi, a high-value product that creates jobs and improves the regional economy. The objective of this research is to analyze the allocation of labor time, costs, revenue, profits, and the efficiency level of the grubi processing business in Tawangmangu District. This descriptive quantitative research was conducted in January-February 2024 using a census method on 20 grubi entrepreneurs. Data were collected through observation, interviews, and documentation. The results showed that the average labor time allocation was 321.87 hours/month, with the molding process being the most time-consuming activity. The business was proven to be efficient and viable with an R/C Ratio of 1.22, generating an average monthly profit of Rp2,885,635.88. These findings highlight that while the business is profitable, the molding process requires evaluation to improve labor efficiency.